2003
DOI: 10.1186/1472-6963-3-21
|View full text |Cite
|
Sign up to set email alerts
|

The requirement for prior consent to participate on survey response rates: a population-based survey in Grampian

Abstract: Background: A survey was carried out in the Grampian region of Scotland with a random sample of 10,000 adults registered with a General Practitioner in Grampian. The study complied with new legislation requiring a two-stage approach to identify and recruit participants, and examined the implications of this for response rates, non-response bias and speed of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 9 publications
8
46
0
1
Order By: Relevance
“…This opens the possibility of examining response rates (strictly 'proportions') according to postcode-derived ecological characteristics such as area deprivation. Several large population-based epidemiological surveys in the UK have used this strategy in recent years, looking at health and non-health outcomes in a range of study designs (1,(6)(7)(8)(9)(10). All eleven examples found strong evidence of lower response rates in more deprived areas, while to our knowledge no studies have found the reverse.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…This opens the possibility of examining response rates (strictly 'proportions') according to postcode-derived ecological characteristics such as area deprivation. Several large population-based epidemiological surveys in the UK have used this strategy in recent years, looking at health and non-health outcomes in a range of study designs (1,(6)(7)(8)(9)(10). All eleven examples found strong evidence of lower response rates in more deprived areas, while to our knowledge no studies have found the reverse.…”
Section: Introductionmentioning
confidence: 89%
“…Most studies simply report non-participation, and no study goes beyond a binary categorisation of non-participation (usually non-contact vs. non-cooperation, although one study compares consenting to receive a questionnaire with subsequently completing that questionnaire (10)). Yet without knowing why people are not taking part, it is very hard to know best how to increase response rates; the best strategy for dealing with non-response because of out-of-date postal addresses will not be the same as the best strategy for dealing with non-response because potential participants do not feel motivated to take part.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Issues regarding consent to participate in NHS research were explored in a Scottish study, 23 revealing serious implications for this kind of research if prior agreement to be approached is required. Agreement to be approached for research (keeping the option to decline consent) as a part of the 'contract' for receiving/providing NHS healthcare would allow the wider re-use of information and would substantially improve the accuracy of epidemiological research.…”
Section: T I O N P R O H I B I T E Dmentioning
confidence: 99%